Rhinometry: spectrum of nasal profile among Nigerian Africans - Jimoh,Rabiu O. (2011)
Nasal parameters measurements are useful in anthropology to distinguish people into racial and ethnic groups. MATERIALS AND METHODS: A cross-sectional survey among Nigerians aged 18 to 70 years of Nigerian parentage randomly selected at the ENT Clinic of the University of Ilorin teaching hospital (U.I.T.H.), Ilorin, Nigeria without gender discrimination had measurement of their nasal parameters done using a sliding caliper: Nasal height, width, tip protrusion, alar thickness, nasal septal thickness and nares diameter. RESULTS: 105 subjects were seen, the age range 18 to 70 years (mean of 28.63 + 13.06 years). There was 58 males and 47 females with a male/female ratio of 1.2:1. The mean nasal width/height (Nasal index -NI) was 90.7 in males and 88.2 in females. Males had a higher NI compared to female (p < 0.03). The commonest type of nasal variability is Type A (70.5%), Platyrrhine nose, Type B (26.7%) especially in females (mesorrhine) and Type C (leptorrhine) (2.8%). CONCLUSIONS: There is significant association between the sex of an individual and type of Nose. Platyrrhine nose, among males and mesorrhine among females, only 2.8% being leptorrhine. The nasal indices were higher in males than in females.